Systemic thrombolysis in the management of pump thrombosis in patients with left ventricular assist devices - Kortekaas, Kirsten A.; den Exter, Paul L.; Beeres, Saskia L. M. A.; Palmen, Meindert; Jukema, J. Wouter; Huisman, Menno V.; Tops, Laurens F. (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular assist device (LVAD) implantation as destination therapy (DT) is a valuable treatment option in patients with end-stage heart failure ineligible for heart transplant. However, this therapy can be complicated by life-threatening pump thrombosis (PT). This case series reports our single-center experience with a structured systemic thrombolysis protocol in case of PT. Consecutive patients undergoing DT LVAD implantation between 2010 and April 2021 at our institution were reviewed and those with PT identified. Clinical, laboratory and LVAD specific data were collected and analyzed retrospectively. All patients with PT were treated with systemic thrombolysis according to a structured bedside protocol. Treatment was defined successful if a patient was alive at 30 days follow-up and free of recurrent PT, stroke or device exchange. Fourteen out of 94 patients experienced a PT after LVAD implantation (11%). Systemic thrombolysis was successful in 10 of 14 patients (71%) at 30 days. Two patients died within 30 days due to a hemothorax and multi-organ failure. In three patients treatment was complicated by a major bleeding; twice a hemothorax (one fatal) and one right calf bleeding. No intracerebral hemorrhage was observed. Three patients experienced a thrombotic complication within 30 days; all recurrent PT. Eleven of the 14 DT patients were discharged home shortly after thrombolysis (average of 11 days). In conclusion, systemic thrombolysis is a reasonable option for life-threatening PT in this vulnerable DT group in whom device exchange is often impossible due to comorbidity.